El desarrollo del Derecho Internacional a través de la función consultiva de la Corte Internacional de Justicia (2021)
The Charter of the United Nations Organization establishes two main functions the International Court of Justice should perform; first, the well known contentious function, which aims to settle differences between Member States, and second, the advisory function, open to the Security Council and to the General Assembly –also to the organisms the General Assembly authorizes–.This article presents general aspects of the advisory function and its importance from a double optic: the consolidation of International Law institutions and its potential utility in the settlement of international disputes –or preventive diplomacy–; to conclude considering ways of extensive use of the advisory function in the international system. These propositions based on more of 60 years of advisory practice of the ICJ.